2018
DOI: 10.1002/14651858.cd009431.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Prokinetics for functional dyspepsia

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 64 publications
0
44
0
8
Order By: Relevance
“…In a recent meta-analysis evaluating the effect of several prokinetics on FD patients, only itopride improved QoL compared with placebo. 26 However, we found that total scores in NDI-K, as well as scores in each individual area of QoL, increased significantly in both groups by week 4, although they were not compared directly with placebo.…”
Section: Discussionmentioning
confidence: 55%
“…In a recent meta-analysis evaluating the effect of several prokinetics on FD patients, only itopride improved QoL compared with placebo. 26 However, we found that total scores in NDI-K, as well as scores in each individual area of QoL, increased significantly in both groups by week 4, although they were not compared directly with placebo.…”
Section: Discussionmentioning
confidence: 55%
“…This may mean that the results of the network are not generalisable to patients with FD consulting in this setting. Finally, unlike previous Cochrane reviews on this topic, 17,18 we did not include RCTs of some prokinetic drugs, such as cisapride or metoclopramide. However, the former has been withdrawn in many countries due to adverse cardiac events, and the latter has had its use restricted to short courses of therapy in Europe due to extra‐pyramidal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous randomised controlled trials (RCTs) of these different drugs vs placebo, and many have demonstrated efficacy in trial‐based systematic reviews and meta‐analyses 16‐19 . However, there have been few head‐to‐head trials of one drug vs another, so the relative efficacy of available treatment options for FD is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, tegaserod also demonstrated to be effective in attenuating dyspeptic symptoms and significantly reduce abdominal pain in functional dyspepsia (FD) patients [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%